THE EFFECT OF STAD UPON STUDENTS WITH DIFFERENT LEVEL OF SELF ESTEEM TOWARD READING COMPREHENSION OF ELEVENTH GRADE STUDENTS OF SMAN 1 KEDIRI TABANAN IN THE ACADEMIC YEAR 2013/2014 - Adi, I N. S. M.; Padmadewi, N. N.; Ratminingsih, N. M. (International Journal of Language and Literature, 2017)
The purpose of the study is to investigate the effect of STAD treatment on reading comprehension in eleventh grade students of SMAN 1 Kediri Tabanan in academic year 2013/2014. Studentsâ self esteem was also put into consideration and was also investigated as the moderator variable. There were 7 classes as the population and by using intact group random sampling, two classes were chosen as the samples of the investigation and were divided into experimental and control group. In total, there were seventy six students who were selected as the representative of the whole population. To collect the data, the study used reading comprehension test which was administered at the end of teaching sessions. In investigating the result, two statistical methods were applied namely descriptive and inferential statistics by using t-test, product moment and one way ANCOVA. At the end of investigation, it was found that, first, there was a significant difference in reading comprehension between the students who were treated by using STAD and the students who were treated by conventional method. Second, viewed from students self esteem which gave minimum contribution toward the difference of reading comprehension âs score between STAD class and conventional class, it was found that there was no significant correlation between self esteem and teaching method, third there was significant correlation between studentsâ self esteem and reading comprehension for all of the students who were taught by STAD and conventional method, there was no correlation between studentsâ self esteem and reading comprehension for the students who were taught by STAD. Last, there was significant correlation between studentsâ self esteem and reading comprehension for the students who were taught by conventional method.